2017
DOI: 10.1161/atvbaha.117.309977
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of AT2 Receptor Prevents SHP-1–Induced VEGF Inhibition and Improves Blood Flow Reperfusion in Diabetic Ischemic Hindlimb

Abstract: Our results suggest that the deletion of AT2 receptor reduced SHP-1 activity and restored VEGF actions, leading to an increased blood flow reperfusion after ischemia in diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(54 citation statements)
references
References 45 publications
3
50
1
Order By: Relevance
“…10 Our previous study showed that the phosphorylation of the VEGFR2, and subsequently Akt was reduced in diabetic animals and completely prevented in the muscle of Agtr2 −/Y mice 4 weeks post surgery. 13 This study enhanced our knowledge that AT2R activation can also affect eNOS in vivo by decreasing both the phosphorylation and expression of eNOS. Numerous studies reported compelling evidence that eNOS uncoupling, which is characterized by the generation of superoxide instead of NO, has been viewed has an important mechanism of endothelial dysfunction in diabetes.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…10 Our previous study showed that the phosphorylation of the VEGFR2, and subsequently Akt was reduced in diabetic animals and completely prevented in the muscle of Agtr2 −/Y mice 4 weeks post surgery. 13 This study enhanced our knowledge that AT2R activation can also affect eNOS in vivo by decreasing both the phosphorylation and expression of eNOS. Numerous studies reported compelling evidence that eNOS uncoupling, which is characterized by the generation of superoxide instead of NO, has been viewed has an important mechanism of endothelial dysfunction in diabetes.…”
Section: Discussionsupporting
confidence: 62%
“…3,18 We have recently reported that diabetes-induced AT2R activation led to increased SHP-1 activity and reduced VEGF actions in the ischaemic muscle after 4 weeks of femoral artery ligation. Since we observed that blood flow reperfusion was almost completely restored after 2 weeks following ischaemia, 13 this study investigated the effect of AT2R ablation on neovascularization in the ischaemic hindlimb in diabetic mice after 14 days post surgery. Deletion of AT2R significantly prevented endothelial cell death in the ischaemic muscle of diabetic mice as compared to diabetic Agtr2 +/Y mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Depletion of AT2 receptor augmented blood flow reperfusion and collateral vessel formation that were associated with SH2 domain-containing phosphatase 1 activity and vascular endothelial growth factor action. 179 …”
Section: Angiotensin II Receptorsmentioning
confidence: 99%